Gravitation and cosmology: Principles and applications of the general theory of relativity - Weinberg, Steven (Wiley, 2014)
Weinberg's 1972 work, in his description, had two purposes. The first was practical to bring together and assess the wealth of data provided over the previous decade while realizing that newer data would come in even as the book was being printed. He hoped the comprehensive picture would prepare the reader and himself to that new data as it emerged. The second was to produce a textbook about general relativity in which geometric ideas were not given a starring role for (in his words) too great an emphasis on geometry can only obscure the deep connections between gravitation and the rest of physics.